Evaluation of the use of leaf fertilizers and growth regulators in winter wheat: A review - Nagyné Mester, Tímea; Pepó, Péter (Acta Agraria Debreceniensis, 2025)
Winter wheat is a leading cereal on a global scale, however, yields remain variable due to increasing weather extremes. This review synthesizes evidence (1971–2024) on the effects of foliar fertilizers and plant growth regulators/biostimulants on wheat growth, yield and quality. Across studies, appropriately timed foliar micronutrient applications (Fe, Mn, Cu, Zn, B, Mo) tend to enhance chlorophyll content, photosynthetic activity, and grain quality traits, while selected copper- and zinc-based products frequently increase grain yield and crude protein. Biostimulants—such as amino acids, humic/fulvic acids and seaweed extracts—generally improve stress tolerance (drought, cold) and may raise grain number and thousand-kernel weight. Plant growth regulators (e.g., lodging control agents) can reduce plant height, strengthen stems and improve stand stability, thereby contributing to yield security. Evidence magnitude varies with soil supply, cultivar, and phenophase-specific timing. We summarize practical windows of application, expected responses, and limitations, and highlight research gaps in standardizing doses and reporting effect sizes. Overall, foliar nutrition and growth regulation are promising tools to increase yield stability and quality under increasingly variable growing conditions.